Characteristics of denitrification and anammox in the sediment of an aquaculture pond - Liu, Xingguo; Gao, Meiyun; Wang, Jie; Gu, Zhaojun; Cheng, Guo-feng (Frontiers in Environmental Science, 2022)
Denitrification and anaerobic ammonium oxidation (anammox) are the key processes of nitrogen removal in aquaculture pond sediment. However, the reaction characteristics remain unclear. In this study, considering the sediment of conventional freshwater fishponds as the object, we set the optimal conditions of organic carbon, temperature, and total nitrates for denitrification and anammox. We found that the abundance and diversity of denitrifying bacteria and anammox bacteria in the two groups were significantly different. Candidatus brocadia is the most important bacteria in aquaculture pond sediments. The removal efficiencies of nitrite (NO2−-N), nitrate (NO3−-N), ammonia nitrogen (NH4+-N), and total organic carbon (TOC) in the anammox optimal conditions group were 97.99%, 93.05%, 54.92%, and 58.82%, respectively; however, those in the denitrification optimal conditions group were 99.82%, 86.10%, 45.74%, and 70.76%, respectively. Comparing each optimal condition, the removal efficiency of NO2−-N and TOC in the denitrification optimal condition groups was higher, whereas those of NO3−-N and NH4+-N were higher in the anammox optimal condition groups. We provide a reference for resolving nitrogen pollution in aquaculture pond sediments.